Improving Arabic Speaking Skill through Mind Mapping Strategy - Miatin Rachmawati; Fitria Nugrahaeni; Lailatul Mauludiyah (Izdihar : Journal of Arabic Language Teaching, Linguistics, and Literature, 2020)
Mind Mapping learning, that uses images and text with a purpose to describe the instructional ideas and concepts, gets lot attention by academicians. A renewal of Arabic learning method and strategy through mind mapping needs to be implemented in Arabic learning. The purpose of this study was to find out the implementation of Mind Mapping to improve students’ Arabic speaking skill. The research method used in this research was descriptive quantitative by emphasizing the improvement of students' speaking abilities and eliminating boredom in learning Arabic. The analysis process presented the results of scores carried out before and after the implementation of mind mapping in Arabic learning. The results of this study were Mind Mapping strategy was effective in learning Arabic, especially in learning speaking skills, because it gave students the courage to bring out new vocabulary they must master. The results were known from the difference between students’ attitude and effectiveness of mind mapping before using this instructional strategy. Based on the percentage results, the success rate of learning rose by 30% and the level of boredom of students in learning decreased by 35%. It means that this strategy can be implemented to improve Arabic speaking skill of students with joyful learning.